Higher number of steps and breaks during sedentary behaviour are associated with better lipid profiles - Sonja Aho; Meri-Sisko Vuoristo; Jani Raitanen; Kirsi Mansikkamäki; Johanna Alanko; Henri Vähä-Ypyä; Riitta Luoto; Pirkko-Liisa Kell; Tommi Vasankari (BMC, 2021)
Abstract Background Physical activity (PA) is known to be associated with lipid profiles and the risk of both cardiovascular diseases and cancer. The aim of this study was to evaluate the association of objectively measured PA, sedentary behaviour (SB), amount of breaks during SB and number of daily steps with serum lipids in a healthy, Finnish, middle-aged, female population. Methods The participants (571) were recruited at mammography screening, target group was women aged 50-60 years. A measurement of PA was done with accelerometer, blood lipid profile was assessed, and questionnaires of participants characteristics were sent to participants. Results The participants with the highest number of daily breaks during SB (≥ 41) had the highest mean concentration of HDL-cholesterol (high density lipoprotein cholesterol, HDL-c) (1.9 mmol/l, standard deviation (SD) 0.4) and the lowest mean concentration of triglycerides (1.0 mmol/l, SD 0.5). HDL-c level was 0.16 mmol/l higher (p < 0.001) in the group with 28-40.9 breaks/day and 0.25 mmol/l higher (p < 0.001) among participants with ≥41 breaks/day than in the group with the fewest breaks during SB (< 28). Those with the most daily steps (≥ 9100) had the highest mean HDL-c level (1.9 mmol/l). HDL-c level was 0.16 mmol/l higher (p < 0.001) among the participants with 5600-9099 steps/day and 0.26 mmol/l higher (p < 0.001) among participants with ≥9100 steps/day than those with the fewest steps (< 5600). The number of daily steps was inversely associated with the triglyceride concentration. From wake-time, participants spent 60% in SB, 18% standing, 14% in light PA, and 9% in moderate-to-vigorous PA (MVPA). PA was associated with serum total cholesterol (TC), HDL-c and triglyceride levels. The mean HDL-c level was the highest in the lowest quartile of SB and in the highest quartile of MVPA. Conclusions To our knowledge, this is the first study showing a high number of objectively measured breaks during SB is associated with a favourable effect on the level of serum lipids, which may later translate into cardiovascular health among middle-aged women. Trial registration This study was registered and approved by the Regional Ethics Committee of Tampere University Hospital in Finland (approval code R15137 ).